The Arab Nationalist Thought of Sate' Al-Husari (Journal of Human Sciences, 2021)
This research, entitled "Arab National Thought by Sate' Al-Hosari", is an attempt to explain and analyze one of his works. We cannot study the nationalist thought of Sate’ Al-Husari in his numerous books, but we will refer to one of them, issued in the period between the two wars. It is the most important of them ever: “Opinions and Conversations on Patriotism and Nationalism,”. It is the main basis of his national thought, and it is a collection of lectures and articles hovering around about patriotism, and nationalism in general, and about Arab patriotism, and nationalism in particular.   Al-Hussary was keen to define its vocabulary, the most important of which are patriotism and patriotism. This means patriotism and patriotism are the love of the nation. He tries to point out the importance of strengthening the national faith and distancing the youth from the spirit of hopelessness, because of the obstacles that the nation faces. He believes that the Arab nation, which rose in the past, must regain its proper position. Al-Hussary draws attention to the danger of the spread of internationalism to the sons of the Arabs. He calls to prevent this tendency from insightful the souls. Regarding Islamic unity and Arab unity, he stresses that Islamic unity is a utopian idea that cannot be achieved in this era, and  that what can be achieved is Islamic brotherhood. As for Arab unity, it is natural and derives its existence from the existence of the Arab nation.